PENGARUH LEBAR SUDUT MANGKOK TERHADAP UNJUK KERJA TURBIN KINETIK - Ujiburrahman Ujiburrahman; Rudy Soenoko; Moch. Agus Choiron (Politeknik Negeri Jakarta, 2019)
Power and efficiency are parameters that show the performance of a kinetic turbine. Previous studies have shown various factors such as flowrate, dimensions and geometry of kinetic turbines are variables that affect the magnitude of power and efficiency. In an effort to improve the performance of kinetic turbines it takes a deep understanding of the factors that influence it. Therefore the purpose of this study was to determine the effect of width variations of bowl blades on kinetic turbine performance. The method used in this study was real experimental on a laboratory scale. Tests were carried out on vertical shaft kinetic turbines with blade width variations of 8 cm, 9 cm and 10 cm. Each turbine is tested on variations of water discharge 45 m3/h, 50 m3/h, 55 m3/h, 60 m3/h and 65 m3/h and in rotation of 80 rpm. The results showed that the width of the bowl affected the performance of the kinetic turbine where the width of the 10 cm bowl blade had a higher performance than the width of the bowl blade 8 cm and 9 cm. The highest performance of kinetic turbines in the variation of the width of the 10 cm bowl blade was obtained at discharge conditions of 65 m3/h. In these conditions the power produced by the kinetic turbine is 12.98 Watts and the efficiency is 35.72%.